AL MAQRIZI'S VIEW ON ISLAMIC ECONOMY AND ITS RELEVANCE TO COVID-19 PANDEMIC IN INDONESIA - Suar, Abi; Meirison, Meirison; Elfia, Elfia; Hayati, Ilda (Nurani, 2020)
The problem of socio-economic phenomena always attracts the attention of various layers of society and individuals because the State's economic stability is the backbone of the material prosperity of the people. It will positively impact development in multiple fields. The Covid-19 Pandemic outbreak that occurred paralyzed not only humans but also paralyzed the Indonesian economy. During Al-Maqriz's life there was starvation and Inflation in the government of the Bani Mamluks in Egypt, Inflation during this period became the main attraction of researchers to make Al-Maqrizi's Economic Thought as a cornerstone of this research theory. This study aims to determine the concepts and work of Al-Maqrizi in his contribution to the Islamic Economy with his relationship with the Covid-19 Pandemic in Indonesia by using the literature study research method and field observations. He was armed with adequate experience as a muhtasib (market watchdog). Al-Maqrizi discussed the problem of Inflation and the role of money in it, a fantastic discussion at that time because it correlated two things that were very rarely done by Muslim and Western thinkers. Inflation occurring in Indonesia is still relatively stable even amid the soaring Rupiah exchange rate when compared with Inflation in the same period before the co-19 epidemic broke out in Indonesia. Keywords: Al-Maqrizi, Islamic Economy, Covid-19, Indonesia